Two-Dimensional Metal Halides for X-Ray Detection Applications - Li, Yumin; Lei, Yutian; Wang, Haoxu; Jin, Zhiwen (Nano-Micro Letters, 2023)
Metal halide perovskites have recently emerged as promising candidates for the next generation of X-ray detectors due to their excellent optoelectronic properties. Especially, two-dimensional (2D) perovskites afford many distinct properties, including remarkable structural diversity, high generation energy, and balanced large exciton binding energy. With the advantages of 2D materials and perovskites, it successfully reduces the decomposition and phase transition of perovskite and effectively suppresses ion migration. Meanwhile, the existence of a high hydrophobic spacer can block water molecules, thus making 2D perovskite obtain excellent stability. All of these advantages have attracted much attention in the field of X-ray detection. This review introduces the classification of 2D halide perovskites, summarizes the synthesis technology and performance characteristics of 2D perovskite X-ray direct detector, and briefly discusses the application of 2D perovskite in scintillators. Finally, this review also emphasizes the key challenges faced by 2D perovskite X-ray detectors in practical application and presents our views on its future development. Highlights: 1 The classification of 2D perovskite is summarized, and the preparation methods of 2D perovskite according to the requirements of X-ray detection materials are introduced. 2 We analyzed the advantages and insufficiency of different devices and introduced improvement measures, including ion migration, charge transfer performance, stability, and 2D/3D heterojunctions. 3 Finally, we introduced the potential preponderances of 2D perovskite in the scintillation detection field; meanwhile, the main challenges facing the practical application of 2D perovskite X-ray detectors are analyzed.